Waiting time Analysis and Satisfaction of Patients with Pharmacy Services in Outpatient Department at Si Songkhram Hospital - มัยวงศ์, กิตติกานต์; Phakdeekul, Wuttiphong; Kedthongma, Warinmad; Phokham , Boonmee (Medical Journal of Sakon Nakhon Hospital, 2024)
This mixed method research aimed to analyze the waiting times and the satisfaction of patients visited pharmacy services, outpatient department, Si Songkhram hospital. The outpatient visit and prescription in fiscal year 2018 and 2019 were 144,335 and 148,733 visits and 86,211 and 91,492 prescriptions, respectively. Data were collected during 1–31 July, 2021 from 380 patients. Collect the waiting time from the time recording of 788 prescriptions, satisfaction data was collected using a questionnaire with a confidence value of 0.95 from 380 patients and qualitative data were collected from a focus group of 7 personnel. The study was conducted during 1-31 July 2021. The quantitative data were analyzed by descriptive statistics, one sample t–test. The qualitative data were analyzed by content analysis. The results showed that 50.80% of patients were males, aged between 31 and 60 years old (69.47%). Of 33.90% was farmer and 61.60% had a chronic disease. Of 61.10% received services at medicine department and 45.80% held the universal coverage medical scheme. The patients’ satisfaction was at level of not satisfied. The confidence of pharmacy was at impressive level. The expectation score of service patients was at the highest level (mean ± S.D. = 3.82 ± 0.23). The average waiting time for medicine receiving was 50.74 ±10.19 minutes which was significantly longer than the standard time (average 20 minutes) assigned by the hospital quality system (p < 0.0001). By the way, the longest waiting time was at the drug preparation step (44.69 ± 9.67 minutes). Therefore, there is an urgent need to develop the working service system of pharmacy services in outpatient department using the guidelines from this study.